The effect of social-media-influencer-popularity on purchase-intention of a fashion-product through emotional attachment - Nabila Auliya Putri; Harmanda Berima Putra (Institute of Computer Science (IOCS), 2024)
This research aims to determine the effect of social media influencer popularity on the purchase intention of a fashion product through emotional attachment. The sample in this research is the general public, who have social media and intend tsso buy fashion products by looking at the popularity of influencers. The number of samples used in this research was 170 respondents. The sampling method uses a purposive sampling technique. Data analysis in this research uses Partial Least Square (PLS). The results of this research show that the popularity of social media influencers has a positive influence on emotional attachment. Emotional attachment has a positive influence on purchase intention. The popularity of social media influencers has a positive influence on purchase intentions. and emotional attachment has a mediating influence on the relationship between social media influencer popularity and purchase intention